PEMBELAJARAN LINGKARAN BERBANTUAN PERMASALAHAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA - Ni Made Dwijayani (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
The purpose of this research was to develope mathematics instructional materials with ICARE model which were valid, practical, and effective. The instructional materials which were developed in this study consisted of mathematics worksheet. Data were collected by using observation sheet of instructional materials implementation, student’s and teacher’s response questionnaire, and problem solving test. The collected data analyzed descriptively. The result of this research showed that the developed mathematics instructional materials are categorized “very high” in validity. Based on the results of try out which were conducted, it was obtained that the instructional materials had fulfilled the practicality aspect. It could be seen from: 1) the instructional implementation on limited try out belonged to practical and instructional implementation on the first and the second field try out belonged to very practical; 2) the use of developed mathematics instructional materials which were observed from student’s response belonged to practical; and 3) teacher’s response towarded the use of mathematics instructional materials belonged to very practical in category. The instructional materials had fulfilled the effectiveness aspects which were seen from: 1) the problem solving skills of students on the first and the second field try out were good in category (had exceeded the standard minimal score). The characteristics of the learning using the developed mathematics instructional materials were: 1) the learning began by introducing students real phenomena and problem in daily life related to the material; 2) giving the students a freedom in giving opinions and discussions; 3) generating social interaction and self-confidence of students, 4) giving the students the learning experience in using GeoGebra; and 5) giving opportunities for students to think about alternative solutions in solving problems.